Fluid-solid interaction of elastic-step type corrugation effects on the mixed convection of nanofluid in a vented cavity with magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2019)
In this study, numerical analysis of mixed convection of CuO-water nanofluid in a cavity with inlet and outlet ports is performed under the effects of inclined magnetic field and step like corrugated elastic walls. The numerical simulation results are obtained by using finite element method. The Arbitrary-Lagrangian-Eulerian method is utilized for the description of the fluid motion with the elastic wall in the fluid-structure interaction model. In the current study, multiple step like corrugation of the wall is considered and it is made elastic which adds additional flexibility for the control of convective heat transfer features of the vented cavity. Effects of various pertinent parameters such as Reynolds number (between 100 and 500), Hartmann number (between 0 and 40), magnetic inclination angle (between 0 degrees and 90 degrees), elastic modulus of the flexible wall (between 5 x 10(4) and 10(8)), number of step-like corrugation (between 1 and 8) and nanoparticle volume fraction (between 0 and 3%) on the fluid flow and heat transfer characteristics are numerically examined. It is observed that for higher value of Reynolds number, local Nusselt number both deteriorates and enhances in various locations along the hot wall whereas the changes in the local Nusselt number are marginal for lower value of Reynolds number. The multiple vortices in the vented cavity are influenced by the variation of magnetic field parameters and number of step like corrugation of the wall while the effects are not significant for the change of magnetic inclination angle. When the value of Hartmann number augments, the average heat transfer reduces until Hartmann number of 30 and increases for the highest value of Hartmann number. The average Nusselt number increment are in the range of 9-9.5% with the nanoparticle addition at the highest volume fraction in the absence and presence of magnetic field. Even though significant changes in the local Nusselt number are observed when the number of step like corrugation increases, it has a deterioration effect on the average heat transfer generally and 5.5% reduction in the average Nusselt number is obtained when the value is increased from 1 to 8.
Keywords: Step corrugation; Elastic wall; Nanofluids; Magnetohydrodynamics; Finite element method; Fluid-solid interaction